THE FORMATION OF “ABNORMAL” STATES OF SUBSTANCE BY THE VACUUM CONDENSATE METHOD: UDC 539.234:546.6+546.83 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
In the result of research of the vacuum condensates, which were prepared by methods of electron-beam and laser evaporation, the model connecting the peculiarities of vacuum condensates formation with main condensation parameters was making. It was shown that degree of crystallites dispersion is one of the determinative parameters of the system state on nano-level consideration of the matter, while the value of the chemical potentials of the agent microquantities, is determined by their real crystallite structure.
Keywords: -